Dictating Change, Shouting Success: Where is Accountability? - Ashfaq Khan (Australasian Accounting, Business and Finance Journal, 2012)
A great body of literature suggests that the poor were better off before the microfinance sector’s paradigm shift of the mid-1990s. The sector’s ‘dependent’ constituents’ focus changed in an effort to cope with the changes dictated by its ‘controlling’ constituents. This paper’s key finding is that the not-for-profit sector, where beneficiaries’ interests are at stake, and the corporate sector, where owners and management are separate, should undergo an externally dictated change only after passing through a regulating agency’s scrupulous check, lest the change harm the sector’s beneficiaries. The paper attempts to create awareness among policy-makers of the need to be thoughtful of the ultimate beneficiaries in similar cases of externally dictated organisational change.
Keywords: Not-for-profit sector; organisational change; controlling and dependent Not-for-profit sector; controlling and dependent